Heat transfer behaviors in round tube with conical ring inserts - Promvonge, P. (My University, 2008)
To increase convection heat transfer in a uniform heat flux tube by a passive method, several conical rings used as turbulators are mounted over the test tube. The effects of the conical ring turbulator inserts on the heat transfer rate and friction factor are experimentally investigated in the present work. Conical rings with three different diameter ratios of the ring to tube diameter (d/D = 0.5, 0.6, 0.7) are introduced in the tests, and for each ratio, the rings are placed with three different arrangements (converging conical ring, referred to as CR array, diverging conical ring, DR array and converging-diverging conical ring, CDR array). In the experiment, cold air at ambient condition for Reynolds numbers in a range of 6000-26,000 is passed through the uniform heat flux circular tube. It is found that the ring to tube diameter ratio and the ring arrays provide a significant effect on the thermal performance of the test tube. The experimental results demonstrate that the use of conical ring inserts leads to a higher heat transfer rate than that of the plain surface tube, and the DR array yields a better heat transfer than the others. The results are also correlated in the form of Nusselt number as a function of Reynolds number, Prandtl number and diameter ratio. An augmentation of up to 197%, 333%, and 237% in Nusselt number is obtained in the turbulent flow for the CR, DR and CDR arrays, respectively, although the effect of using the conical ring causes a substantial increase in friction factor. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Conical ring turbulator; Friction factor; Heat exchanger; Heat transfer; Turbulent/reverse flow